Religious Sentiment and Conflict Mitigation in Indonesia: A Qualitative Urban-Rural Case Study - Ikhwan Sawaty (Edumaspul: Jurnal Pendidikan, 2024)
Religious sentiment-based conflicts pose a serious challenge to maintaining social cohesion in Indonesia, a country historically known for its religious and cultural diversity. Religious sentiments emerging in public spaces—whether through direct interactions or digital media—often trigger horizontal tensions, particularly in socially vulnerable areas. This study aims to examine conflict mitigation strategies based on religious sentiment in selected strategic urban and rural regions prone to latent conflict. Employing a qualitative approach with a multi-site case study design, the research was conducted in five areas: Jakarta, Surakarta, Ambon, Poso, and Tasikmalaya. Data were collected through in-depth interviews with religious and community leaders, participatory observation, and analysis of local policy documents. The findings indicate that effective mitigation is strongly influenced by three key factors: the strength of interfaith social networks, the mediation capacity of local actors, and the presence of adaptive policies that respond to local dynamics. In urban areas, the roles of the Interfaith Harmony Forums (FKUB) and digital religious moderation campaigns were pivotal, whereas in rural areas, local wisdom-based approaches and community reconciliation were found to be more effective. This study recommends strengthening local actor capacities and integrating both structural and cultural approaches in the formulation of religious conflict mitigation policies.